Famílias camponesas e sucessão no nordeste brasileiro : limitações à permanência dos jovens no ofício de agricultor - Santos, Elaíne Cristina dos (Mundo Agrario.)
This article aims to analyze the establishment of the succession pattern of peasant families, based on the permanence of young peasants and the development of the "farming profession". The methodology used was the foundation of the case study. The research was developed in the municipality of Pedro Velho, state of Rio Grande do Norte, Northeast Brazil. The sample corresponded to 16porciento of peasant family farmers and data were collected through the application of questionnaires with 28 rural families (fathers/mothers, children, totaling 56 respondents). The work shows the problem of succession to the agricultural profession, exposing limitations and desires of peasant family farmers and their children who try to remain in the agricultural activity. Although there is no defined succession pattern, most young people expressed a desire to continue working as a farmer. However, their life projects are frustrated by limited productive capacity, lack and discontinuity of public rural development policies, especially access to land.